The effect of fascia iliaca block on postoperative pain and analgesic consumption for patients undergoing primary total hip arthroplasty: a meta-analysis of randomized controlled trials - Wenli Dai; Xi Leng; Xiaoqing Hu; Jin Cheng; Yingfang Ao (Journal of Orthopaedic Surgery and Research, 2021)
Abstract Background The primary aim of this systematic review and meta-analysis was to compare postoperative pain, analgesic consumption, and complications after fascia iliaca block (FIB) versus control for patients undergoing primary total hip arthroplasty (THA). Second, we compared the outcomes of FIB versus placebo. Finally, we sought to evaluate pain and analgesic consumption after preoperative and postoperative FIB. Methods We performed a systematic literature search in MEDLINE, Embase, Scopus, Web of Science, Google Scholar, ClinicalTrials.gov , and CENTRAL through February 2021 to identify randomized controlled trials (RCTs) that evaluated the efficacy of FIB versus control for patients undergoing primary THA. All analyses were conducted on intent-to-treat data with a random-effects model. Results Twelve RCTs with a total of 815 patients were included. There was no difference in postoperative pain (P = 0.64), analgesic consumption (P = 0.14), or complication rate (P = 0.99) between FIB and control groups. Moreover, no difference in postoperative pain (P = 0.26), analgesic consumption (P = 0.06), or complication rate (P = 0.71) was found between FIB and placebo. Moreover, sensitivity analysis suggested that no significant difference in postoperative pain, analgesic consumption, or complication rate was present between FIB and control in studies that used preoperative and postoperative FIB. Conclusion FIB was not found to be superior to placebo or various anesthetic techniques for patients undergoing primary THA, as measured by postoperative pain, analgesic consumption, and complications.